2011
DOI: 10.1007/s12078-011-9108-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Body Odor Signals by the Human Brain

Abstract: Brain development in mammals has been proposed to be promoted by successful adaptations to the social complexity as well as to the social and non-social chemical environment. Therefore, the communication via chemosensory signals might have been and might still be a phylogenetically ancient communication channel transmitting evolutionary significant information. In humans, the neuronal underpinnings of the processing of social chemosignals have been investigated in relation to kin recognition, mate choice, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 93 publications
(108 reference statements)
1
87
0
2
Order By: Relevance
“…For instance, if smells can prime different social identities, then perhaps smells could be used to alter compliance with group norms or even discrimination. Another fascinating line of research has focused on the role of chemosensory signals (found in body odors and tears) in social communication (Frumin et al, 2015;Gelstein et al, 2011;Pause, 2012). It is currently assumed that chemosensory signals are processed by the olfactory system in humans.…”
Section: Implications For Understanding Perceptionmentioning
confidence: 99%
“…For instance, if smells can prime different social identities, then perhaps smells could be used to alter compliance with group norms or even discrimination. Another fascinating line of research has focused on the role of chemosensory signals (found in body odors and tears) in social communication (Frumin et al, 2015;Gelstein et al, 2011;Pause, 2012). It is currently assumed that chemosensory signals are processed by the olfactory system in humans.…”
Section: Implications For Understanding Perceptionmentioning
confidence: 99%
“…Furthermore, because we set out to compare effects of three different androstene compounds, and in view of the results in which we find compound-specific effects, it is possible that individual androstene compounds (or their relative concentrations) may have functional effects in modulating social interactions. Androstenes, which are produced in higher quantities in males, might be involved in intersexual and intrasexual communication (Pause, 2012;Lübke and Pause, 2015), and particularly in modulating responses to words in social contexts that are associated with specific emotions.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have been shown to occur outside conscious awareness and to induce specific neural and behavioural reactions in humans. Therefore, it is postulated that through psychological sweating in the axilla the experience of stress can be chemosensorily transmitted from the sender to the receiver [94]. …”
Section: Functionmentioning
confidence: 99%